ANALISA JARINGAN DISTRIBUSI TEGANGAN MENENGAH DENGAN SISTEM SINGLE WIRE EARTH RETURN UNTUK WILAYAH TERTINGGAL, TERDEPAN DAN TERLUAR - Rakesh Vaswani; Ridho Alpha Kusuma (Universitas 17 Agustus 1945 Jakarta, 2022)
Indonesia's rural electrification rate (RER) is still low. This is due to the high cost of installing a conventional three-phase or single-phase power supply in distributed rural loads. However, the Rural Energy Agency and the National Utility have made many efforts to address this issue. To this end, this document proposes a Single Wire Earth Return (SWER) electrification scheme for the electrification of a selected village, namely Serang, Banten. Field data were collected and used to design a potential SWER distribution network. A mathematical model representing SWER for Serang, Banten was developed and simulations were performed to determine soil potential and soil resistance. These two are important every time you install a HEAVY line. In addition, a technical and economic comparison was made in order to determine the short-term costs of the proposed SWER with the existing single-phase two-wire (SPTW) system. The technical and economic analysis shows that the proposed SWER system will achieve a cost saving of 50% compared to the installation of the SPTW system for Serang Banten electrification.